Community-Based Mental Health and Substance Use Services for People Leaving Prison: Equity and Inclusion Strengths and Limitations in Specialized Service Inventory Development. - Watson, Tara Marie; Benassi, Paul Victor; Agic, Branka; Maharaj, Asha; Sockalingam, Sanjeev (Community Mental Health Journal, 2023)
Community reentry from prison is a challenging process, especially for persons with lived and living experience of mental health concerns. Access to appropriate community-based care for those leaving prison is a key part of improving health equity for this population. Our work to develop a cross-Canada inventory of active community mental health and substance use services for criminal justice-involved persons represents a valuable example for others hoping to conduct projects that are similar in nature and scope. We describe the strengths and limitations of our health equity-informed, multi-pronged approach to service inventory development, highlighting the importance of considering and addressing search- and stakeholder-related biases. Investment of time and resources is critical to ensuring comprehensive and inclusive identification of community-based mental health services and meaningful resource development.